Teacher education journal - Salandanan, Gloria G (Quezon Avenue, Quezon City, 2001)
It is upon us, teacher educators, to fully equip our teachers with adequate and up-to-date knowledge of subject content, hone their skills in a wide repertoire of instructional methodologies and foster desirable values and attitudes
Keywords: Teacher education